Organizational Behavior in the Satu Voice Student Activity Unit Hadrah Division at UIN Sayyid Ali Rahmatullah Tulungagung - Haris Syamsuddin Haris; Nadia Zulfa Khoiriya; Safira Mardhotilah; Moh. Nurul Huda (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze organizational behavior and work culture within the Satu Voice Student Activity Unit (UKM) Hadrah Division at UIN Sayyid Ali Rahmatullah Tulungagung, which serves as a platform for students to develop their talents in Islamic music and vocal performance. The study focuses on organizational dynamics, including communication patterns, leadership style, member behavior, and the work culture that shapes the organization's daily activities. The findings reveal that formal communication within the organization functions effectively and supports organizational coordination. However, informal communication among members remains relatively limited outside organizational activities, resulting in interpersonal relationships that tend to be functional rather than socially cohesive. In terms of leadership, the head of the organization adopts a democratic leadership style by encouraging members to express their opinions and participate in decision-making processes. Nevertheless, members' active participation in organizational activities remains suboptimal. Overall, the Satu Voice Hadrah Division has successfully established a well-structured organizational system that facilitates students' talent development. However, the organization continues to face challenges in enhancing member engagement and strengthening its organizational culture through the promotion of informal communication and greater social cohesion among its members.